WHOLE GRAIN CONSUMPTION AND ITS DETERMINANTS IN MALAYSIAN MEDICAL STUDENTS (Proceedings of the International Conference on Public Health, 2017)
Whole grain consumption is associated with several health benefits. Little is known however, about whole grain consumption patterns in medical students in Malaysia. The objective of this study was to assess whole grain intake pattern and its determinants amongst Malaysian medical students. A cross sectional study investigating whole grain intake amongst 151 medical students in a private medical University in Malaysia was conducted. A self-administered questionnaire was used to assess sociodemographic variables, the whole grain intake pattern and the knowledge and attitudes towards whole grain intake. The prevalence of reported whole grain intake in the past 3 months was 51%.Chinese ethnicity, readiness to adhere to Malaysian food pyramid and self-preparation of food and eating at home were significantly associated with whole grain consumption. However, the primary determinants of food choice like education, knowledge and affordability did not seem to influence whole grain consumption. Whole grain consumption is relatively low amongst Malaysian medical students. Cultural background and self-belief influence this practice despite being from the medical fraternity. Efforts are needed to bridge the knowledge – practice gap by assessing the barriers to whole grain consumption in order to design effective initiatives to promote an increase in whole grain consumption.
Keywords: whole grain consumption, medical students, practice